IMPLEMENTASI MANAJEMEN LAYANAN KHUSUS BIMBINGAN DAN KONSELING DI MADRASAH TSANAWIYAH - Darwipat, Nurul Fajriah; Habibah, Sitti (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2024)
This study examines the implementation of special service management guidance and counseling. The purpose of this research is to find out the implementation of special service management guidance and counseling in Madrasah Tsanawiyah Takalar State. This research approach is qualitative with qualitative descriptive research type. Data collection techniques in the form of observations, interviews and documentation. Data analysis techniques use data reduction, data exposure and conclusion drawing. Checking the validity of data using trianggulasi and trianggulasi data techniques. Based on the results of previous research, the researchers concluded that the implementation of special service management guidance and counseling in Takalar State MTs has not been implemented due to the lack of guidance and counseling teachers in the school and cooperation between principals, teachers in the field of study and BK teachers is not good in implementing the implementation of special service management guidance and counseling. There are four areas of guidance services in Takalar State MTs: (1) Academic Field, (2) Personal Field, (3) Social Field and (4) Career Field.